Stereotypical architecture of the stem cell niche is spatiotemporally established by miR-125-dependent coordination of Notch and steroid signaling. - Yatsenko, A.S.; Shcherbata, H.R. (Development, 2018)
Stem cell niches act as signaling platforms that regulate stem cell self-renewal and sustain stem cells throughout life; however, the specific developmental events controlling their assembly are not well understood. Here, we show that during Drosophila ovarian germline stem cell niche formation, the status of Notch signaling in the cell can be reprogrammed. This is controlled via steroid-induced miR-125 , which targets a negative regulator of Notch signaling, Tom. Thus, miR-125 acts as a spatiotemporal coordinator between paracrine Notch and endocrine steroid signaling. Moreover, a dual security mechanism for Notch signaling activation exists to ensure the robustness of niche assembly. Particularly, stem cell niche cells can be specified either via lateral inhibition, in which a niche cell precursor acquires Notch signal-sending status randomly, or via peripheral induction, whereby Delta is produced by a specific cell. When one mechanism is perturbed due to mutations, developmental defects or environmental stress, the remaining mechanism ensures that the niche is formed, perhaps abnormally, but still functional. This guarantees that the germline stem cells will have their residence, thereby securing progressive oogenesis and, thus, organism reproduction.